Water vapor line parameters from 6450 to 9400 cm-1; Journal of Quantitative Spectroscopy and Radiative Transfer; Vol. 136 - Régalia L.; Oudot C.; Mikhailenko S. N. Semen Nikolaevich; Wang L.; Thomas X.; Jenouvrier A.; Heyden P. Von der (2014, 2014)
Title screen